Analisis Pengendalian Kualitas Kernel Pada Stasiun Nut Dan Kernel Di PT X: Analisis Pengendalian Kualitas Kernel Pada Stasiun Nut Dan Kernel Di PT X - Hasbullah, Muhammad Hasyim; Darmawan, Muhammad Indra; Linangsari, Titis; Ningsih, Yuliana; Meldayanoor, Meldayanoor (Jurnal Teknologi Agro-Industri, 2024)
Kernel processing at PT X has a problem where the resulting kernel has a high level of impurities that can affect the yield of palm kernel oil (PKO) to be processed. Threrefore, it is necessary to control kernel stations, using Statistical Process Control (SPC). The purpose of this research is to analyze kernel quality control at Nut and Kernel Stasions. The method in this study is Statistical Process Control (SPC) using 3 statistical tools namely check sheet, histogram and fishbone diagram. The results of the analysis of the tudy can be known the quality of the kernel in the parameters of dirt leves ecceeding the standards, namely by an average of 9.06% where the most dominant factor is the machine, 2 the main cause is the process of separation on the nutrition of the ripple mill is not optimal. PT X is preferred to be ecamined and regular anda regular ttreatments on the ripple mill machine every morning and the provision of directives to the operators to always adhere to the DOP applicable at each station.